High-strength antifriction wear-resistant corrosion-resistant coating, metal composite material, preparation method and application

By using ultrasonic assisted concave texture processing and convex texture processing methods in eutectic high-entropy alloy coatings, the BCC content is increased, and the problem of insufficient BCC content in the coating is solved, thereby improving the overall performance of the coating and realizing the anti-fouling self-cleaning function.

CN119900024APending Publication Date: 2025-04-29TIANJIN UNIV OF TECH & EDUCATION (TEACHER DEV CENT OF CHINA VOCATIONAL TRAINING & GUIDANCE)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510027326.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing eutectic high entropy alloy coatings have less BCC content, resulting in insufficient strength, corrosion resistance, hardness and wear resistance of the material.

Method used

The concave texture processing is assisted by ultrasonic to improve the internal temperature field of the coating, thereby increasing the BCC content, and further induced the formation of BCC through the processing of the convex texture.

Benefits of technology

It significantly improves the overall performance of the coating, including strength, corrosion resistance, hardness, wear resistance and friction reduction, and gives the coating anti-fouling self-cleaning function.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119900024A_ABST
    Figure CN119900024A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength antifriction, wear-resistant and corrosion-resistant coating, a metal composite material, a preparation method and application. The preparation method of the coating comprises the following steps: (1) firstly, preparing a laser cladding layer; the laser cladding layer is an eutectic high-entropy alloy mainly comprising an FCC phase; secondly, concave texture machining is conducted on the laser cladding layer, then convex texture machining is conducted, and the high-strength antifriction wear-resistant corrosion-resistant coating is obtained; wherein the concave texture processing is carried out under the assistance of ultrasonic waves. According to the method, concave texture machining is carried out through ultrasonic assistance, the characteristic that the internal temperature field of the coating in concave texture machining can be improved through ultrasound is utilized, so that the BCC content is increased, and further, formation of BCC is further induced through heat input of convex texture machining. The invention also finds that concave texture processing and convex texture processing which are sequentially carried out on the laser cladding layer have a synergistic effect, and the prepared coating has excellent strength, corrosion resistance, hardness, wear resistance and antifriction performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating preparation, and in particular to a high-strength, friction-reducing, wear-resistant and corrosion-resistant coating, a metal composite material, and a preparation method and application thereof. Background Art

[0002] Marine equipment needs to operate stably in harsh marine environments such as high pressure, high humidity, high salt, and strong ultraviolet rays, while maintaining a long service life and high reliability. Therefore, existing marine equipment materials can no longer meet the growing performance requirements. Surface modification technology is a method of physically, chemically or mechanically treating the surface of a material to improve the wear resistance, corrosion resistance, thermal conductivity and other properties of the material surface to adapt to different environments and needs. Ultra-high-speed laser cladding technology has the advantages of metallurgical bonding of the coating, high density, controllable thickness, and low heat input to the substrate. The coating prepared by ultra-high-speed laser cladding is expected to meet the performance requirements of the surface of marine equipment.

[0003] Compared with traditional alloys, the performance of multi-principal alloys is determined by multiple elements, and they preferentially form solid solutions rather than intermetallic compounds, so they have better comprehensive performance. Eutectic high entropy alloy is a type of multi-principal alloy. Compared with single-phase high entropy alloys, it breaks the limitation of single-phase high entropy alloys between strength and ductility, and combines the advantages of various phases such as the excellent ductility of FCC phase, the high hardness of BCC phase, and the excellent wear resistance of Laves phase. The comprehensive performance of the coating has been greatly improved. AlCoCrFeNi 2.1 It is a typical two-phase eutectic high entropy alloy, which combines the advantages of FCC and BCC single-phase high entropy alloys and has excellent strength and ductility. However, relevant studies have shown that there is only a small amount of nano-scale BCC precipitation inside the coating, and the main phase is still FCC. Therefore, the performance of coatings that require high strength, corrosion resistance, and wear resistance still needs to be improved. In order to solve the above problems, many researchers have conducted extensive research on how to increase the BCC content, among which the change of heat input is considered to be an effective means, such as laser cladding and ultra-high-speed laser cladding of AlCoCrFeNi 2.1 The coating is prepared. Due to the change in heat input, the element diffusion in the coating prepared by ultra-high-speed laser cladding changes significantly and the BCC content is significantly increased. However, the present invention has found through research that the BCC content produced in the coating prepared by laser cladding alone is still relatively small, and the main phase is still FCC. The comprehensive performance of the coating needs to be further improved. Summary of the invention

[0004] The object of the present invention is to provide a high-strength, anti-friction, wear-resistant and corrosion-resistant coating, a metal composite material, and a preparation method and application. The present invention uses ultrasound to assist in concave texture processing. The use of ultrasound can improve the characteristics of the temperature field inside the coating during concave texture processing, thereby increasing the BCC content. Further, the heat input of convex texture processing further induces the formation of BCC. The present invention also finds that the concave texture processing and convex texture processing performed sequentially on the laser cladding layer have a synergistic effect, which can significantly improve the comprehensive performance of the coating. The coating prepared by the method of the present invention has excellent strength, corrosion resistance, hardness, wear resistance and friction reduction performance.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The first aspect of the present invention is to provide a method for preparing a high-strength friction-reducing, wear-resistant and corrosion-resistant coating, comprising the following steps:

[0007] Step (1) first prepares a laser cladding layer; the laser cladding layer is a eutectic high entropy alloy mainly composed of FCC phase, wherein the mass content of the FCC phase in the high entropy alloy is 80%-93%;

[0008] Step (2) first performs concave texture processing on the laser cladding layer and then performs convex texture processing to obtain the high-strength, friction-reducing, wear-resistant and corrosion-resistant coating; wherein the concave texture processing is performed under the assistance of ultrasound.

[0009] As a preferred embodiment,

[0010] Step (1), the composition of the laser cladding layer is AlCoCrFeNi 2.1 、Al 0.5 FeCu 0.7 NiCoCr, MgMoNbFeTi2Y or AlCoCrFeNiTi; and / or,

[0011] Step (2), fix the laser cladding layer in an ultrasonic device, and then use a laser marking machine to perform concave texture processing on the laser cladding layer; spread the dried alloy powder on the surface of the sample after the concave texture processing, and use laser 3D printing to realize convex texture processing.

[0012] As a more preferred embodiment,

[0013] The polished laser cladding layer is fixed in an ultrasonic device, and then a laser marking machine is used to perform concave texture processing on the laser cladding layer; the surface after the concave texture processing is polished, and the dried alloy powder is spread on the surface of the sample after the concave texture processing and polishing, and the convex texture processing is realized by laser 3D printing.

[0014] In the present invention, the purpose of grinding is the existing conventional operation, which is to make the surface smooth or remove the oxide layer on the surface, so as to make the coating preparation effect better.

[0015] As a preferred embodiment,

[0016] The preparation of the laser cladding layer comprises the following steps:

[0017] Step (a): placing a laser head on the surface of the base material to be clad;

[0018] Step (b): conveying coating material to the surface of the substrate material to be clad;

[0019] Step (c): The laser head emits laser light toward the surface of the base material to be clad and provided with the coating material, so as to prepare a laser cladding layer on the surface of the base material.

[0020] As a preferred embodiment,

[0021] In step (a), the laser head is offset in the X-axis direction, with an angle of 10°-30° with the surface of the substrate material to be clad; and / or,

[0022] The distance between the laser head and the surface of the base material to be clad is 20-24 mm; and / or,

[0023] Step (b), the powder feeding amount of the coating material is 15.2-17.8 g / min; and / or,

[0024] Step (c), the laser power is 2000W-2500W; and / or,

[0025] The wavelength of the laser is 635-650nm.

[0026] As a preferred embodiment,

[0027] In step (2), when performing concave texture processing, the parameters of the ultrasonic device are:

[0028] The frequency of the ultrasound used is 20-30 kHz; and / or,

[0029] The ultrasonic vibration direction is perpendicular to the laser scanning direction; and / or,

[0030] The output power of ultrasound is 1400-1700W.

[0031] As a preferred embodiment,

[0032] Step (2), when performing concave texture processing, the parameters of the laser marking machine are:

[0033] The diameter of the laser spot is 60-80 μm; and / or,

[0034] The power of the laser is 60-120W; and / or,

[0035] The scanning speed of the laser is set to 50-80 mm / s; and / or,

[0036] The laser's air jump speed is 2500-3500 mm / s; and / or,

[0037] The pattern after concave texturing is an equidistantly arranged pattern (preferably a plurality of identical patterns arranged equidistantly), wherein the pattern is a square, a regular hexagon or a circle; the shortest lateral spacing between the patterns is 120-150 μm, the side length or diameter of the pattern is 420-450 μm, and the texture depth of the pattern is 50-60 μm.

[0038] As a preferred embodiment,

[0039] In step (2), when performing convex texture processing, the parameters of 3D printing using laser are:

[0040] The dry alloy powder used is AlCoCrFeNi 2.1 、Al 0.5 FeCu 0.7 NiCoCr, MgMoNbFeTi2Y, AlCoCrFeNiTi powder; particle size 15-53 μm; and / or,

[0041] The diameter of the laser spot is 200 μm-220 μm; and / or,

[0042] The laser power is 180-220W; and / or,

[0043] The laser scanning rate is 10-20 mm / s; and / or,

[0044] The pattern after convex texturing is an equidistantly arranged pattern (preferably a plurality of identical patterns arranged equidistantly), wherein the pattern is a square, a regular hexagon or a circle; the shortest lateral spacing between the patterns is 50-150 μm, the side length or diameter of the pattern is 350-450 μm, and the texture height of the pattern is 50-60 μm.

[0045] The second aspect of the present invention is to provide a high-strength, anti-friction, wear-resistant and corrosion-resistant coating prepared by the method described in the first aspect of the present invention.

[0046] The third aspect of the present invention is to provide a metal composite material, comprising a base material and a high-strength, friction-reducing, wear-resistant and corrosion-resistant coating disposed on the base material;

[0047] The base material is marine steel material; preferably marine steel material such as DH36, EH550, FH690, etc.;

[0048] The high-strength anti-friction, wear-resistant and corrosion-resistant coating is the high-strength anti-friction, wear-resistant and corrosion-resistant coating described in the second aspect of the present invention.

[0049] The fourth aspect of the present invention is to provide an application of the high-strength anti-friction, wear-resistant and corrosion-resistant coating as described in the second aspect of the present invention in aerospace and marine equipment.

[0050] At present, eutectic high entropy alloys such as AlCoCrFeNi 2.1 The prepared coating is mainly FCC phase with only a small amount of BCC phase, which will result in the material having excellent ductility but insufficient strength, corrosion resistance, hardness and wear resistance. The present invention uses ultrasound to assist in concave texture processing. Ultrasound can be used to improve the characteristics of the internal temperature field of the coating during concave texture processing, thereby increasing the BCC content. Further, the heat input of convex texture processing further induces the formation of BCC. The present invention also finds that the concave texture processing and convex texture processing performed sequentially on the laser cladding layer also have a synergistic effect, which can significantly improve the comprehensive performance of the coating. The coating prepared by the method of the present invention can not only further improve the strength, corrosion resistance, hardness and friction and wear resistance of the coating, but also make the coating surface have the function of anti-fouling and self-cleaning, thereby realizing the preparation of an integrated coating with strength, corrosion resistance, high hardness and friction and wear resistance.

[0051] Beneficial effects: The present invention uses ultrasound to assist in concave texture processing. The use of ultrasound can improve the characteristics of the temperature field inside the coating during concave texture processing, thereby increasing the BCC content. Furthermore, the heat input of convex texture processing further induces the formation of BCC. The present invention also finds that the concave texture processing and convex texture processing performed sequentially on the laser cladding layer have a synergistic effect, which can significantly improve the comprehensive performance of the coating. The coating prepared by the method of the present invention has excellent strength, corrosion resistance, hardness, wear resistance and friction reduction performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 Schematic diagram of the pattern after concave texture processing is performed on Example 1 of the present invention;

[0053] Figure 2 Schematic diagram of the pattern after concave texture processing is performed on Example 2 of the present invention;

[0054] Figure 3 Schematic diagram of the pattern after concave texture processing is performed on Example 3 of the present invention;

[0055] Figure 4 Schematic diagram of the pattern after concave texture processing is performed on Example 4 of the present invention;

[0056] Figure 5Schematic diagram of the pattern after concave texture processing is performed on Example 5 of the present invention;

[0057] Figure 6 Schematic diagram of the pattern after concave texture processing is performed on Example 6 of the present invention. DETAILED DESCRIPTION

[0058] The present invention is further described in detail below through the accompanying drawings and specific embodiments.

[0059] Example 1

[0060] The AlCoCrFeNi2.1 eutectic high entropy alloy powder (spherical powder with a particle size of 15-53μm and a purity of 99%) was dried in a drying oven and cooled to room temperature. In the embodiment, the composite coating was prepared on the EH690 substrate by laser cladding, and the coating was prepared by a coaxial powder feeding method; the protective gas used was inert gas argon (purity 99.999%), the powder feeding amount was selected to be 16.3g / min, the protective gas flow rate was 12L / min, and the surface of EH690 was polished with sandpaper to remove the surface oxide layer. The coating was prepared using fiber laser cladding equipment. After the laser head was aligned with the surface of EH690 to be clad by the robot controller, the laser head was slightly tilted so that it was at a certain angle (30°) to the surface to be clad; use

[0061] The controller adjusts the distance between the laser head and the substrate surface so that the defocusing amount between the laser head and the substrate surface (i.e., the distance between the laser head and the surface of the base material to be clad) is always maintained at 22 mm. At this time, the powder can be ensured to converge at the laser beam convergence point and intersect. The coating overlap rate is set. The optimal forming quality of the present invention is selected to have an overlap rate of 85%. The high-speed reciprocating platform is turned on to set the platform moving speed. The selected speed is 230 mm / s. External control is selected, and the powder feeding switch is controlled by the program in the robot controller; the laser (635 nm) power in the laser system is set to 2200 W, and the light waiting time is set to 2 s. After completing the above steps, the program is started to prepare the coating. During the cladding process, the powder feeder, protective gas, and laser system are observed.

[0062] First, the prepared AlCoCrFeNi 2.1 The coating surface is polished to remove the surface oxide and facilitate the marking machine to perform texture processing. 2.1The coating is fixed in an ultrasonic device (the ultrasonic device is a metal plate with grooves that can vibrate ultrasonically, and it has a clamp inside, through which the preheated substrate is embedded in the grooves of the metal plate), and then a laser marking machine is used to perform square concave texture processing on the laser cladding layer. When performing square concave texture processing, the frequency of the ultrasound used is 20kHz; the vibration direction of the ultrasound is perpendicular to the laser scanning direction; the output power of the ultrasound is 1500W; the diameter of the laser spot is 70μm, the laser processing parameters are 70W, the laser scanning speed is set to 60mm / s, and the air jump speed is 2500mm / s. The shortest lateral spacing between the square concave textures obtained by the above method is 150μm, the side length is 450μm, and the texture depth is 50μm. Specifically, Figure 1 shown.

[0063] Before the 3D printing experiment, the surface of the sample with the concave texture was polished with a grinder to make it smooth, and the textured sample was ultrasonically cleaned in alcohol for 20 minutes. The experimental steps of 3D printing are as follows: the treated sample is placed on a movable workbench, and the dried AlCoCrFeNi 2.1 Eutectic high entropy alloy powder (spherical powder with a particle size of 15-53μm and a purity of 99%) is spread on the sample surface, the laser spot is 200μm, the laser power is 220W, the laser scanning rate is 10mm / s, the spacing between the circular convex textures is 200μm, the diameter is 500μm, and the texture height is 50μm.

[0064] Example 2

[0065] First, the AlCoCrFeNi prepared in Example 1 2.1 The coating surface is polished to remove the surface oxide and facilitate the marking machine to perform texture processing. 2.1 The coating is fixed in an ultrasonic device, and then a laser marking machine is used to process the hexagonal concave texture of the laser cladding layer. When processing the hexagonal concave texture, the frequency of the ultrasound used is 25kHz; the vibration direction of the ultrasound is perpendicular to the laser scanning direction; the output power of the ultrasound is 1600W, and the laser processing parameter is 80W; the diameter of the laser spot is 80μm, the laser scanning speed is set to 70mm / s, and the jump speed is 2800mm / s; the spacing between the hexagonal concave textures obtained by the above method is 150μm, the side length is 500μm, and the texture depth is 50μm, as shown in the following figure. Figure 2 shown.

[0066] The same convex texture processing parameters as those in Example 1 are used.

[0067] Example 3

[0068] First, the AlCoCrFeNi prepared in Example 12.1 The coating surface is polished to remove the surface oxide and facilitate the marking machine to perform texture processing. 2.1 The coating is fixed in an ultrasonic device, and then a laser marking machine is used to process the circular concave texture of the laser cladding layer. When processing the circular concave texture, the frequency of the ultrasound used is 26kHz; the vibration direction of the ultrasound is perpendicular to the laser scanning direction; the output power of the ultrasound is 1600W; the diameter of the laser spot is 60μm, the laser processing parameters are 100W, the laser scanning speed is set to 60mm / s, and the jump speed is 3200mm / s. The circular concave textures obtained by the above method have a spacing of 150μm, a diameter of 450μm, and a texture depth of 50μm. Figure 3 shown.

[0069] The same convex texture processing parameters as those in Example 1 are used.

[0070] Example 4

[0071] First, the AlCoCrFeNi prepared in Example 1 2.1 The coating surface is polished to remove the surface oxide and facilitate the marking machine to perform texture processing. 2.1 The coating is fixed in an ultrasonic device, and then a laser marking machine is used to process the circular concave texture of the laser cladding layer. When processing the circular concave texture, the frequency of the ultrasound used is 24kHz; the vibration direction of the ultrasound is perpendicular to the laser scanning direction; the output power of the ultrasound is 1700W; the diameter of the laser spot is 75μm, the laser processing parameters are 120W, the laser scanning speed is set to 50mm / s, and the jump speed is 3500mm / s. The circular concave textures obtained by the above method have a spacing of 200μm, a diameter of 500μm, and a texture depth of 50μm. Specifically, Figure 4 shown.

[0072] The same convex texture processing parameters as those in Example 1 are used.

[0073] Example 5

[0074] First, the AlCoCrFeNi prepared in Example 1 2.1 The coating surface is polished to remove the surface oxide and facilitate the marking machine to perform texture processing. 2.1The coating is fixed in an ultrasonic device, and then a laser marking machine is used to process the circular concave texture of the laser cladding layer. When processing the circular concave texture, the frequency of the ultrasound used is 28kHz; the vibration direction of the ultrasound is perpendicular to the laser scanning direction; the output power of the ultrasound is 1500W; the diameter of the laser spot is 70μm, the laser processing parameters are 80W, the laser scanning speed is set to 70mm / s, and the jump speed is 3000mm / s. The circular concave textures obtained by the above method have a spacing of 100μm, a diameter of 400μm, and a texture depth of 50μm. Figure 5 shown.

[0075] The same convex texture processing parameters as those in Example 1 are used.

[0076] Example 6

[0077] First, the AlCoCrFeNi prepared in Example 1 2.1 The coating surface is polished to remove the surface oxide and facilitate the marking machine to perform texture processing. 2.1 The coating is fixed in an ultrasonic device, and then a laser marking machine is used to process the circular concave texture of the laser cladding layer. When processing the circular concave texture, the frequency of the ultrasound used is 30kHz; the vibration direction of the ultrasound is perpendicular to the laser scanning direction; the output power of the ultrasound is 1400W; the diameter of the laser spot is 75μm, the laser processing parameters are 60W, the laser scanning speed is set to 80mm / s, and the jump speed is 2800mm / s. The circular concave textures prepared by the above method have a spacing of 50μm, a diameter of 350μm, and a texture depth of 50μm. Specifically, Figure 6 shown.

[0078] The same convex texture processing parameters as those in Example 1 are used.

[0079] Example 7

[0080] The concave texture processing adopts the same concave texture processing method as Example 5.

[0081] Before the 3D printing experiment, the surface of the concave texture sample prepared in Example 6 was polished with sandpaper, and the texture sample was ultrasonically cleaned in alcohol for 25 minutes. The experimental steps of 3D printing are as follows: the treated sample is placed on a movable workbench, and the dried AlCoCrFeNi 2.1 Eutectic high entropy alloy powder (spherical powder with a particle size of 15-53μm and a purity of 99%) is spread on the sample surface, the diameter of the laser spot is 200μm, the laser power is 210W, the laser scanning rate is 14mm / s, and the circular convex textures obtained by the above method have a spacing of 150μm, a diameter of 450μm, and a texture height of 50μm.

[0082] Example 8

[0083] The concave texture processing adopts the same concave texture processing method as Example 5.

[0084] Before the 3D printing experiment, the surface of the concave texture sample prepared in Example 6 was polished with sandpaper, and the texture sample was ultrasonically cleaned in alcohol for 40 minutes. The experimental steps of 3D printing are as follows: the treated sample is placed on a movable workbench, and the dried AlCoCrFeNi 2.1 Eutectic high entropy alloy powder (spherical powder with a particle size of 15-53μm and a purity of 99%) is spread on the sample surface, the laser spot is 200μm, the laser power is 200W, the laser scanning rate is 16mm / s, and the circular convex textures obtained by the above method have a spacing of 100μm, a diameter of 400μm, and a texture height of 50μm.

[0085] Example 9

[0086] The concave texture processing adopts the same concave texture processing method as Example 5.

[0087] Before the 3D printing experiment, the surface of the concave texture sample prepared in Example 6 was polished with sandpaper, and the texture sample was ultrasonically cleaned in alcohol for 30 minutes. The experimental steps of 3D printing are as follows: the treated sample is placed on a movable workbench, and the dried AlCoCrFeNi 2.1 Eutectic high entropy alloy powder (spherical powder with a particle size of 15-53μm and a purity of 99%) is spread on the surface of the sample. The diameter of the laser spot is 200μm, the laser power is 180W, and the laser scanning rate is 20mm / s. The circular convex textures obtained by the above method have a spacing of 50μm, a diameter of 350μm, and a texture height of 50μm.

[0088] Comparative Example 1

[0089] It adopts the same laser cladding layer and convex texture processing method as Example 5, that is, only the convex texture processing is performed on the laser cladding layer.

[0090] Comparative Example 2

[0091] It adopts the same laser cladding layer and concave texture processing method as Example 5, that is, concave texture processing is only performed on the laser cladding layer.

[0092] Comparative Example 3

[0093] It adopts the same laser cladding layer processing method as Example 5, that is, only the laser cladding layer is prepared.

[0094] Comparative Example 4

[0095] The same processing method as in Example 2 is used, with the only difference being that the concave texture processing is not performed under ultrasonic assistance.

[0096] The coatings prepared in the above examples and comparative examples were subjected to performance tests, and the results are shown in Table 1.

[0097] Table 1

[0098] <![CDATA[Hardness (HV 0.5 )]]> <![CDATA[Wear volume (mm 3 )]]> Friction coefficient Example 1 275 0.016 0.66 Example 2 279 0.015 0.63 Example 3 296 0.013 0.59 Example 4 284 0.014 0.61 Example 5 308 0.010 0.52 Example 6 298 0.012 0.55 Example 7 306 0.011 0.53 Example 8 322 0.008 0.49 Example 9 314 0.009 0.51 Comparative Example 1 250 0.018 0.69 Comparative Example 2 257 0.017 0.68 Comparative Example 3 232 0.020 0.72 Comparative Example 4 264 0.017 0.67

[0099] From the comparison of the results of Examples 1-3, it can be seen that under the same convex texture processing conditions and the arrangement of concave texture patterns with equal spacing and equal side lengths or equal diameters, when the concave texture pattern is a circular concave texture, the comprehensive performance of the prepared coating is better.

[0100] From the comparison of the results of Examples 3-6, it can be seen that under the same convex texture processing conditions and the same circular concave texture patterns, among the circular concave texture patterns with different spacings and diameters, the circular concave texture of Example 5 has a spacing of 100 μm, a diameter of 400 μm, and a texture depth of 50 μm, and the prepared coating has better comprehensive performance.

[0101] From the comparison of the results of Examples 5, 7-9, it can be seen that when the same circular concave texture sample is used, different convex texture processing conditions result in different coating performance. Among them, the circular convex textures of Example 8 have a spacing of 100 μm, a diameter of 400 μm, and a texture height of 50 μm, and the overall performance of the prepared coating is better.

[0102] In addition, by comparing the results of comparative examples 1-3 and example 5, it can be seen that the comprehensive performance of the coating prepared by the embodiment of the present invention after the concave texture processing and the convex texture processing on the laser cladding layer is significantly better than the performance of the coating prepared by the single concave texture processing or the convex texture processing, indicating that the concave texture processing and the convex texture processing on the laser cladding layer in the present invention have a synergistic effect, and the performance of the coating prepared by the embodiment of the present invention is better. The possible reasons are speculated to be: first, the convex texture processing also has heat input, which makes the elements inside the coating diffuse again to form more BCC, increases the content of inducing the transformation of the FCC phase to the BCC phase, and increases the total content of BCC. Specifically, the FCC phase and BCC phase contents of the high-strength anti-friction, wear-resistant and corrosion-resistant coatings prepared in Example 5, Examples 7-9 and Comparative Example 2 of the present invention are shown in Table 2; second, although the concave texture can store abrasive particles to reduce the friction coefficient, the friction contact area between the coating and the grinding pair becomes smaller, and the local wear is serious, resulting in a decrease in wear resistance. The invention adds a convex texture on the basis of a concave texture, which can increase the contact area between the coating and the grinding pair. At the same time, the concave texture below can further increase the space for storing abrasive particles, thereby achieving both friction reduction and wear resistance.

[0103] Table 2

[0104]

[0105]

[0106] By comparing the results of Comparative Example 4 with those of Example 2, it can be seen that the coating prepared by ultrasonically assisted concave texturing processing in the present invention has better performance.

[0107] In summary, the current eutectic high entropy alloys such as AlCoCrFeNi 2.1 The prepared coating is mainly FCC phase with only a small amount of BCC phase, which will result in the material having excellent ductility but insufficient strength, corrosion resistance, hardness and wear resistance. The present invention uses ultrasound to assist in concave texture processing. Ultrasound can be used to improve the characteristics of the temperature field inside the coating during concave texture processing, thereby increasing the BCC content. Furthermore, the heat input of convex texture processing further induces the formation of BCC. The present invention finds that the concave texture processing and convex texture processing performed sequentially on the laser cladding layer also have a synergistic effect, which can significantly improve the comprehensive performance of the coating. The coating prepared by the method of the present invention can not only further improve the strength, corrosion resistance, hardness and friction and wear resistance of the coating, but also make the coating surface have the function of anti-fouling and self-cleaning, thereby realizing the preparation of an integrated coating with strength, corrosion resistance, high hardness and friction and wear resistance.

[0108] The above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing a high-strength, anti-friction, wear-resistant and corrosion-resistant coating, characterized in that: The following steps are involved: Step (1) first prepares a laser cladding layer; the laser cladding layer is a eutectic high entropy alloy mainly composed of FCC phase, wherein the mass content of the FCC phase in the high entropy alloy is 80%-93%; Step (2) first performs concave texture processing on the laser cladding layer and then performs convex texture processing to obtain the high-strength, friction-reducing, wear-resistant and corrosion-resistant coating; wherein the concave texture processing is performed under the assistance of ultrasound.

2. The method for preparing the high-strength anti-friction, wear-resistant and corrosion-resistant coating according to claim 1, characterized in that: Step (1), the composition of the laser cladding layer is AlCoCrFeNi 2.1 、Al 0.5 FeCu 0.7 NiCoCr, MgMoNbFeTi2Y or AlCoCrFeNiTi; and / or, Step (2), fix the laser cladding layer in an ultrasonic device, and then use a laser marking machine to perform concave texture processing on the laser cladding layer; spread the dried alloy powder on the surface of the sample after the concave texture processing, and use laser 3D printing to realize convex texture processing.

3. The method for preparing the high-strength anti-friction, wear-resistant and corrosion-resistant coating according to claim 2, characterized in that: The preparation of the laser cladding layer comprises the following steps: Step (a): placing a laser head on the surface of the base material to be clad; Step (b): conveying coating material to the surface of the substrate material to be clad; Step (c): The laser head emits laser light toward the surface of the base material to be clad and provided with the coating material, so as to prepare a laser cladding layer on the surface of the base material.

4. The method for preparing the high-strength anti-friction, wear-resistant and corrosion-resistant coating according to claim 3, characterized in that: In step (a), the laser head is offset in the X-axis direction, with an angle of 10°-30° with the surface of the substrate material to be clad; and / or, The distance between the laser head and the surface of the base material to be clad is 20-24 mm; and / or, Step (b), the powder feeding amount of the coating material is 15.2-17.8 g / min; and / or, Step (c), the laser power is 2000W-2500W; and / or, The wavelength of the laser is 635-650nm.

5. The method for preparing the high-strength anti-friction, wear-resistant and corrosion-resistant coating according to claim 2, characterized in that: In step (2), when performing concave texture processing, the parameters of the ultrasonic device are: The frequency of the ultrasound used is 20-30 kHz; and / or, The ultrasonic vibration direction is perpendicular to the laser scanning direction; and / or, The output power of ultrasound is 1400-1700W.

6. The method for preparing the high-strength anti-friction, wear-resistant and corrosion-resistant coating according to claim 2, characterized in that: Step (2), when performing concave texture processing, the parameters of the laser marking machine are: The diameter of the laser spot is 60-80 μm; and / or, The power of the laser is 60-120W; and / or, The scanning speed of the laser is set to 50-80 mm / s; and / or, The laser's air jump speed is 2500-3500 mm / s; and / or, The graphics after concave texture processing are arranged equidistantly, wherein the graphics are square, regular hexagon or circle; the shortest lateral spacing between the graphics is 120-150 μm, the side length or diameter of the graphics is 420-450 μm, and the texture depth of the graphics is 50-60 μm.

7. The method for preparing the high-strength anti-friction, wear-resistant and corrosion-resistant coating according to claim 2, characterized in that: In step (2), when performing convex texture processing, the parameters of 3D printing using laser are: The dry alloy powder used is AlCoCrFeNi 2.1 、Al 0.5 FeCu 0.7 NiCoCr, MgMoNbFeTi2Y, AlCoCrFeNiTi powder; particle size 15-53 μm; and / or, The diameter of the laser spot is 200 μm-220 μm; and / or, The laser power is 180-220W; and / or, The laser scanning rate is 10-20 mm / s; and / or, The graphics after convex texture processing are equidistantly arranged graphics, wherein the graphics are squares, regular hexagons or circles; the shortest lateral spacing between graphics is 50-150μm, the side length or diameter of the graphics is 350-450μm, and the texture height of the graphics is 50-60μm.

8. A high-strength, friction-reducing, wear-resistant and corrosion-resistant coating prepared by the method according to any one of claims 1 to 7.

9. A metal composite material, characterized in that: It comprises a base material and a high-strength friction-reducing, wear-resistant and corrosion-resistant coating disposed on the base material; The base material is marine steel material; The high-strength anti-friction, wear-resistant and corrosion-resistant coating is the high-strength anti-friction, wear-resistant and corrosion-resistant coating according to claim 8.

10. Use of the high-strength anti-friction, wear-resistant and corrosion-resistant coating according to claim 8 in aerospace and marine equipment.